PENGARUH RASIO LIKUIDITAS DAN SOLVABILITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN TERINDEKS LQ45 - Umar, Iyam; Junus, Onang; Masiaga, Novaliastuti (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2024)
Financial statement analysis is needed to assess the company's financial performance and compare financial conditions from year to year. This analysis helps in making strategic decisions based on financial performance. Previous studies have shown various findings on the influence of financial variables such as CR (Current Ratio), Debt to Equity Ratio (DER), Earning per Share (EPS), and Return on Equity (ROE) on stock prices and the company's financial performance. This study aims to determine a). To determine the liquidity ratio's effect on the Financial Performance of LQ45 indexed companies b). To determine the Solvency Ratio's effect on Financial Performance in LQ45 indexed companies. This study uses quantitative data. The data presented are from the results of financial reports of companies indexed in LQ45 obtained through the Indonesia Stock Exchange. The conclusions of the analysis are as follows: a). The liquidity ratio does not have a partial effect on the company's financial performance, but the solvency and profitability ratios have an effect. Simultaneously, the three ratios affect the financial performance of companies indexed in LQ45. b). The company is experiencing an unhealthy liquidity ratio, which indicates a lack of ability to pay short-term and long-term debts every year. Although there is an increase in fluctuating ability, it still has not reached a good level, especially in debt payments by banking companies